An Empirical Study Assessing Variances in Dysfunctional Audit Behavior with Experience - Sandra KHALIL (Communications of International Proceedings, 2021)
The paper explores auditors’ attitudes towards dysfunctional audit behaviors (DAB) in relation to different time pressures such as time budget and time deadline. It particularly investigates changes in DAB with the accumulation of years of experience. The paper initially surveyed a group of auditors joining an audit firm in the UK. The same group of auditors is surveyed again after gaining three years of experience. The purpose is to compare their attitudes towards DAB when they were inexperienced auditors to their attitudes when they become experienced. Results show that experienced auditors have a greater tendency to engage in DAB than junior auditors.
Keywords: Dysfunctional Audit Behavior; Time pressure; Experience